Role of FNA with core biopsy or cell block in patients with nodular lymphocyte‐predominant Hodgkin lymphoma. Issue 8 (28th April 2020) - Gupta, Srishti; Long, Steven R.; Natkunam, Yasodha; Kong, Christina S.; Gupta, Neel K.; Gratzinger, Dita
Abstract : Background: Nodular lymphocyte‐predominant Hodgkin lymphoma (NLPHL) represents a diagnostic challenge on surgical excisional or incisional biopsy. Classification is further challenging on fine needle aspiration (FNA) material accompanied by needle core and/or cell block biopsy (FNA+core/CB). Methods: The authors studied all FNA+core/CB and surgical excisional or incisional biopsies to evaluate for lymphoma in patients who had a prior history of NLPHL or subsequent diagnosis of NLPHL over a 5‐year period from 2012 through 2016. Results: Patients who ultimately were diagnosed with NLPHL represented <0.5% of those who underwent FNA+core/CB for an initial suspicion of lymphoma. FNA+core/CB resulted in a definitive diagnosis in 7 of 13 cases, and surgical excisional or incisional biopsy specimens resulted in a definitive diagnosis in 13 of 13 cases (chi‐square statistic, 9.6; P  = .002). At initial diagnosis, FNA+core/CB was negative in 2 cases and atypical or suspicious in 3 cases; all 5 of those patients required surgical excisional or incisional biopsy for a definitive lymphoma diagnosis. By contrast, patients who underwent FNA+core/CB for recurrent lymphoma required surgical excisional or incisional biopsy in only 1 of 8 cases (chi‐square statistic, 9.5; P  = .002). Flow cytometry was positive for a light‐chain–restricted B‐cell population in only 1 of 11 biopsies that were involved by lymphoma. Conclusions: Surgical excisional or incisional biopsy remains the gold standard for NLPHL diagnosis and for distinguishing progression to a T‐cell/histiocyte–rich large B‐cell lymphoma pattern. At a tertiary cancer center with routine collaborative diagnosis of lymphoma on FNA+core/CB by cytopathologists and hematopathologists, FNA+core/CB performs well to assess for recurrent or transformed NLPHL, rarely requiring subsequent surgical excisional or incisional biopsy. FNA+core/CB has limited sensitivity in the initial diagnosis setting. Abstract : Fine‐needle aspiration testing accompanied by needle core and/or cell block biopsy mostly performs well in patients with an established diagnosis of nodular lymphocyte‐predominant Hodgkin lymphoma (NLPHL) to assess for recurrent or transformed disease but has limited sensitivity for NLPHL in the initial diagnosis setting, thus requiring surgical excisional or incisional biopsy for definitive diagnosis. Patients with a history of NLPHL may recur with a T‐cell/histiocyte‐rich large B‐cell pattern, and patients with T‐cell/histiocyte‐rich large B‐cell lymphoma may recur with NLPHL, necessitating sufficient intact tissue for histology and immunohistochemistry as well as expert hematopathology review to distinguish these clinically important patterns.